Asymmetric dimethylarginine (ADMA) elevation and arginase up‐regulation contribute to endothelial dysfunction related to insulin resistance in rats and morbidly obese humans. (4th March 2016) - El Assar, Mariam; Angulo, Javier; Santos‐Ruiz, Marta; Ruiz de Adana, Juan Carlos; Pindado, María Luz; Sánchez‐Ferrer, Alberto; Hernández, Alberto; Rodríguez‐Mañas, Leocadio
Abstract : Key points: The presence of insulin resistance (IR) is determinant for endothelial dysfunction associated with obesity. Although recent studies have implicated the involvement of mitochondrial superoxide and inflammation in the defective nitric oxide (NO)‐mediated responses and subsequent endothelial dysfunction in IR, other mechanisms could compromise this pathway. In the present study, we assessed the role of asymmetric dimethylarginine (ADMA) and arginase with respect to IR‐induced impairment of endothelium‐dependent vasodilatation in human morbid obesity and in a non‐obese rat model of IR. We show that both increased ADMA and up‐regulated arginase are determinant factors in the alteration of thel ‐arginine/NO pathway associated with IR in both models and also that acute treatment of arteries with arginase inhibitor or withl ‐arginine significantly alleviate endothelial dysfunction. These results help to expand our knowledge regarding the mechanisms of endothelial dysfunction that are related to obesity and IR and establish potential therapeutic targets for intervention. Abstract: Insulin resistance (IR) is determinant for endothelial dysfunction in human obesity. Although we have previously reported the involvement of mitochondrial superoxide and inflammation, other mechanisms could compromise NO‐mediated responses in IR. We evaluated the role of the endogenous NOS inhibitor asymmetric dimethylarginine (ADMA) and arginase with respect to IR‐induced impairment ofl ‐arginine/NO‐mediated vasodilatation in human morbid obesity and in a non‐obese rat model of IR. Bradykinin‐induced vasodilatation was evaluated in microarteries derived from insulin‐resistant morbidly obese (IR‐MO) and non‐insulin‐resistant MO (NIR‐MO) subjects. Defective endothelial vasodilatation in IR‐MO was improved byl ‐arginine supplementation. Increased levels of ADMA were detected in serum and adipose tissue from IR‐MO. Serum ADMA positively correlated with IR score and negatively with pD2 for bradykinin. Gene expression determination by RT‐PCR revealed not only the decreased expression of ADMA degrading enzyme dimethylarginine dimethylaminohydrolase (DDAH)1/2 in IR‐MO microarteries, but also increased expression of arginase‐2. Arginase inhibition improved endothelial vasodilatation in IR‐MO. Analysis of endothelial vasodilatation in a non‐obese IR model (fructose‐fed rat) confirmed an elevation of circulating and aortic ADMA concentrations, as well as reduced DDAH aortic content and increased aortic arginase activity in IR. Improvement of endothelial vasodilatation in IR rats byl ‐arginine supplementation and arginase inhibition provided functional corroboration. These results demonstrate that increased ADMA and up‐regulated arginase contribute to endothelial dysfunction as determined by the presence of IR in human obesity, most probably by compromising arginine availability. The results provide novel insights regarding the mechanisms of endothelial dysfunction related to obesity and IR and establish potential therapeutic targets for intervention. Key points: The presence of insulin resistance (IR) is determinant for endothelial dysfunction associated with obesity. Although recent studies have implicated the involvement of mitochondrial superoxide and inflammation in the defective nitric oxide (NO)‐mediated responses and subsequent endothelial dysfunction in IR, other mechanisms could compromise this pathway. In the present study, we assessed the role of asymmetric dimethylarginine (ADMA) and arginase with respect to IR‐induced impairment of endothelium‐dependent vasodilatation in human morbid obesity and in a non‐obese rat model of IR. We show that both increased ADMA and up‐regulated arginase are determinant factors in the alteration of thel ‐arginine/NO pathway associated with IR in both models and also that acute treatment of arteries with arginase inhibitor or withl ‐arginine significantly alleviate endothelial dysfunction. These results help to expand our knowledge regarding the mechanisms of endothelial dysfunction that are related to obesity and IR and establish potential therapeutic targets for intervention.